The physical demands of Super League rugby: Experiences of a newly promoted franchise - Evans, S. D.; Brewer, C.; Haigh, J. D.; Lake, M.; Morton, J. P.; Close, G. L. (European Journal of Sport Science, 2015)
The physical match demands for a newly promoted European Super League (ESL) squad were analysed over a full season using global positioning systems. Players were classified into four positional groups: outside backs (OB), pivots (PIV), middle unit forwards (MUF) and wide running forwards (WRF). MUF covered less total distance (4318 ± 570 m) than WRF (6408 ± 629 m), PIV (6549 ± 853) and OB (7246 ± 333 m) (P < 0.05) and less sprint distance (185 ± 58 m) than WRF (296 ± 82 m), PIV (306 ± 108) and OB (421 ± 89 m; P < 0.05), likely attributable to less playing time by MUF (47.8 ± 6.6 min) compared with WRF (77.0 ± 9.0 min), PIV (72.8 ± 10.6 min) and OB (86.7 ± 3.4 min; P < 0.05). Metres per minute were greater for MUF (90.8 ± 2.2 m.min-1) compared with OB (83.6 ± 2.8 m.min-1) and WRF (83.4 ± 2.4 m.min-1; P = 0.001) although not different from PIV (90.2 ± 3.3 m.min-1; P > 0.05). WRF (36 ± 5) and MUF (35 ± 6) were involved in more collisions than OB (20 ± 3) and PIV (23 ± 3; P < 0.05). The high-speed running and collision demands observed here were greater than that previously reported in the ESL, which may reflect increased demands placed on the lower ranked teams. The present data may be used to inform coaches if training provides the physical stimulus to adequately prepare their players for competition which may be especially pertinent for newly promoted franchises.